Well-being of the Tourists in Varanasi City: A Perceptional Analysis - Dhanraj Gownamani (National Geographical Journal of India, 2022)
Tourism is a social activity in which the relation between the hosts and guests are in the central position (Jarkko Saarinen et al., 2008). Keeping the guests at the core, this paper highlights the perception of the incoming tourists of Varanasi city. Sample Survey had been conducted and through interview schedule the data had been collected for an analysis of perception of the tourists. Statistical analysis had been carried out for the data collected. This present paper tries to highlight the problems and perspectives of tourists under different components. The findings suggest that the proper regulation and the maintenance in the quality of services are very essential in order to attract more tourists especially foreign tourists.